Di Benedetto, Antonio. 2016. Escritos periodísticos. Investigación, selec., pról. y notas Liliana Reales. Buenos Aires: Adriana Hidalgo Editora. 594 pp. - Granata, Gladys (2016)
Fil: Granata, Gladys. Universidad Nacional de Cuyo